Goiter with NIFTP Lesion Associated with an Accessory Thyroid as an Uncommon Anatomical Variant: Insights from a Case and Review of the Literature - Bachar, Amine; Malik, Baallal Zarhouni; El Azhari, Ilias; Essaidi, Zakaria; Elabbassi, Taoufik; Bensardi, Fatima Zahra (British Journal of Healthcare and Medical Research, 2024)
Thyroidectomy is a usual surgery done by surgeons around the world, its difficulty remains in the anatomical variation of the cervical region and the multiple aspect of the thyroid pathology. In this optic we report a rare multinodular goiter with an accessory thyroid associated with a NIFTP lesion. This unique association make a double challenge firstly in surgery and secondly in the fellow up.We present the experience of our department and a review of the literature to draw attention of surgeons and pathologists about these variant of embryology and pathology.